G. S. Achilles in the Trojan Chronicles of Dictys and Dares - Silva, Gelbart Souza [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2022)
We aim to analysis Achilles in the ancient novels written in Latin known by the titles Ephemeris belli Troiani and De excidio Troiae historia. The two anonymous works respectively dating from the fourth and fifth centuries A.D. recount the Trojan War from the point of view of a first-person narrator and engage in intertextual dialogue with the mythological and epic canon, in particular with the Homeric epics. Our examination points out a de-heroized Achilles in these two works, and his passion for Polyxena plays an important role in this (de)construction of the heroic character.
Keywords: Achilles; Ancient Novel; De excidio Troiae historia; Ephemeris belli Troiani